Politeness Strategies Applied by the Characters of Princess Diaries Movie - Anang Fatkhurozi (Nuris Journal of Education and Islamic Studies, 2022)
This study examines the politeness strategies of the characters in the Princess Diaries movie. The data were utterances of Mia and her grandmother, the main characters in the Princess Diaries movie. The analysis is based on Scollon and Scollon's politeness theory. As a result, the researcher found that Mia and Her Grandmother employed two types of politeness: involvement and independent strategies. Mia used twenty politeness strategies, including four involvement strategies and sixteen independent strategies. Her grandmother, on the other hand, employed fifteen politeness strategies: twelve involvement strategies and three independent strategies. This study may inspire additional researchers to investigate politeness strategies not only in two characters but also in various films, theories, or methods. Additionally, it is hoped that research on politeness strategies will expand our understanding of how linguistic aspects, particularly in English, are applied.